Adequação da regionalização da saúde: a integralidade e os vazios assistenciais no estado do Paraná - Rocha, Flávio de Matos (2021)
The objective of this work is to analyze the adequacy of the regionalization of health in the state of Paraná as a mechanism capable of guaranteeing the comprehensiveness of SUS' medium-complexity care. Integrality is desired through the operationality of the health region being able to provide all services corresponding to the medium complexity and when this does not occur, the referral to another health region is carried out. The system with its regionalized and hierarchical network achieves the precepts of integrality. When a Health Region needs to forward medium-complexity hospitalizations to another Health Region, there is a discussion on the adequacy of health regionalization through the dropout rate. Quantitative research characterized by the descriptive-explanatory type was adopted, organized from the literature review on health regionalization and on the theoretical framework of regionalization theories (Theory of Central Places and Growth Poles) and the formation of the urban network Brazilian. The means of research is bibliographical, adopting the analysis of the adequacy of regionalization by measuring the dropout rate, and documentary by using the methodology of Ordinance GM/MS n.º 1.631/15 for analysis of care gaps. As a result, the largest health regions recorded deficits in most specialties, while they had lower dropout rates, understanding that dropout rates as a measure of adequacy measurement do not necessarily indicate problems of regionalization adequacy. The discussion of this thesis expands the possibility of reflecting on the process of building the regionalization of health, and how it is important to achieve not only comprehensiveness, but also the guarantee of citizenship for the population, as more efficient is the organization of the health system.